Effect of Shale Sample Particle Size on Pore Structure Obtained from High Pressure Mercury Intrusion Porosimetry - Zhiye Gao; Longfei Duan; Qinhong Hu; Shuling Xiong; Tongwei Zhang (Geofluids)
With the rapid development of unconventional oil and gas, the pore structure characterization of shale reservoirs has attracted an increasing attention. High pressure mercury intrusion porosimetry (HPMIP) has been widely used to quantitatively characterize the pore structure of tight shales. However, the pore structure obtained from HPMIP could be significantly affected by the sample particle size used for the analyses. This study mainly investigates the influence of shale sample particle size on the pore structure obtained from HPMIP, using Mississippian-aged Barnett Shale samples. The results show that the porosity of Barnett Shale samples with different particle sizes obtained from HPMIP has an exponentially increasing relation with the particle size, which is mainly caused by the new pores or fractures created during shale crushing process as well as the increasing exposure of blind or closed pores. The amount and proportion of mercury retention during mercury extrusion process increase with the decrease of shale particle size, which is closely related to the increased ink-bottle effect in shale sample with smaller particle size. In addition, the fractal dimension of Barnett Shale is positively related to the particle size, which indicates that the heterogeneity of pore structure is stronger in shale sample with larger particle size. Furthermore, the skeletal density of shale sample increases with the decrease of particle size, which is possibly caused by the differentiation of mineral composition during shale crushing process.